Investigation of Iridium-Based OER Catalyst Layers in a GDE Half-Cell Setup: Opportunities and Challenges - Geuß, Moritz; Milosevic, Maja; Bierling, Markus; Löttert, Lukas; Abbas, Dunia; Escalera-López, Daniel; Lloret, Vicent; Ehelebe, Konrad; Mayrhofer, Karl J.J.; Thiele, Simon; Cherevko, Serhiy (Journal of The Electrochemical Society, 2023)
To achieve widespread commercialization of proton exchange membrane (PEM) water electrolyzers, the optimization of iridium (Ir) utilization is crucial. Traditional full-cell-based approaches are time-consuming and labor-intensive. In this work, the feasibility of using a gas diffusion electrode (GDE) half-cell as an alternative to full-cell setups for accelerated investigation of Ir-oxide-containing anode catalyst layers (CLs) is scrutinized. Using CLs composed of Ir oxides of different intrinsic oxygen evolution reaction (OER) activity as a probe, we show that a GDE can successfully reveal the differences in the performance of the CLs. Comparison of the results obtained in the GDE to those from rotating disk electrode (RDE) and full-cell membrane electrode assembly (MEA) measurements indicate that GDE data can closely mimic both setups. However, essential discrepancies are observed between GDE and MEA, which are linked to differences in the catalyst layer | membrane interface and the presence of liquid electrolyte in the GDE setup. Our findings reveal that even though the direct comparison of the OER performance to full-cell measurements is still partially hampered, GDE half-cell setups can already be used for fundamental assessments and accelerated screening of electrocatalysts and CLs at relevant current densities up to 1.5 A cm−2
CRIS-Team Scopus Importer:2023-12-01